Resolution Of The Psychological Conflict Of The Characters Razhan And Sameer In The Series Jayyibat Al-Eid - M. Bagus Rahmandhika Putra; Fadlil Yani Ainusyamsi; Ade Ahmad Suprianto (Hasanuddin University, 2025)
Literary works usually show personal and social struggles that mirror the complexities of human life. An example of this is the Jayyibat al-Eid series, which shows how the characters Razan and Sameer face challenges from cultural differences, family expectations, and their own wishes. This study aims to find out and describe the types of psychological conflict that Razan and Sameer face and to examine the ways they use ego defense mechanisms to deal with these struggles. The problems they face are examined using Kurt Lewin's theory of psychological conflict and Sigmund Freud's idea of ego defense mechanisms. The method used is is descriptive qualitative with observation and note-taking techniques, through dialogue, monologue, and the characters' actions that reveal the dynamics of inner conflict. The result shows that there are three main types of conflict: approach–approach conflict, avoidance–avoidance conflict, and approach–avoidance conflict. To handle these conflicts, the characters use different defense mechanisms like rationalization, reaction formation, denial, and repression. These strategies help them feel less anxious and keep their self-esteem intact. These results show that the emotional struggles in stories not only highlight how complex the characters are but also mirror the social and cultural situations that affect people's lives.